Identification of low birth weight babies by birth weight-independent anthropometric measures - Kagithapu, Surender; Gudur, Vijaykumar; Ravikumar, Chodavarapu (Indian Journal of Child Health, 2018)
Introduction: Birth weight (BW) is the single most important factor that affects neonatal mortality and infant and childhood morbidity. Most of the deliveries in rural areas are conducted at home, often by traditional birth attendants and relatives, where the facility to weigh the baby is not possible. There is a constant search for simple and effective method to identify at-risk low BW (LBW) babies. Objectives: The objectives of this study were to identify a single or combination of anthropometric data that reliably identify LBW babies. Materials and Methods: This was a cross-sectional study conducted in neonatal care unit of a teaching hospital. The study subjects included 141 singleton newborns with gestational age of between 32 and 42 weeks and within 24 h of birth were included in the study. Newborns that were sick or having congenital anomalies were excluded from the study. In all newborns, gestational age assessment and anthropometric data measurement were done within 24 h of birth by trained residents. Results: Male (54.0%) and female babies (46.0%) were similar in proportion. The mean BW was 2.54±0.53 kg and 43.3% were LBW babies (<2.5 kg). Calf circumference (CC), chest circumference (CHC), midarm circumference (MAC), head circumference (HC), and crown-to-heel length (CHL) showed significant and high positive correlation of 0.887, 0.871, 0.807, 0.77, and 0.724, respectively, with BW. The cutoff values corresponding with a BW of <2.5 kg with high sensitivity were as follows: CC ?10.5 cm, CHC ?32 cm, MAC ?10 cm, HC ?33.8 cm, and CHL ?50 cm. Conclusions: CC was the single most useful anthropometric measure to predict LBW. Its sensitivity of 100% with relatively higher specificity of 67.5% indicates its ability mainly to rule out LBW in a baby, if CC is >10.5 cm.